Houses : habitats & home life - Macdonald, Fiona; Salariya, David (New York : F. Watts, 1994)
Traces the development of housing from early shelter to the 20th century and beyond.
Includes index.
Wilson's Junior High School.
6.6
5-8
Keywords: Dwellings -- History -- Juvenile literature; Manners and customs -- History -- Juvenile literature; Vernacular architecture -- History -- Juvenile literature; Dwellings -- History; Houses -- History